PENYULUHAN DENGAN METODE DEMONSTRASI DAN MEDIA BOOKLAT BERPENGARUH TERHADAP KOMPETENSI SCREENING COVID-19 TIM SATGAS - Cahyaningrum, Ika Cahyaningrum (Universitas Tribhuwana Tunggadewi, 2022)
Patients who were confirmed positive in Malang Regency, East Java, data as of July 10, 2021 showed as many as 4,441 cases, this data showed an increase of 24 cases from the previous date, with data on active cases as of July 10 as many as 449 cases which experienced an increase of 148 cases. Active cases are people who are still considered sick or are still being treated (Kominfo 2021b). The government urges schools at the PPKM 1-3 level to implement Limited Face-to-face Learning (PTMT) in the 2021/2022 school year. In carrying out this program, the role of the COVID-19 Task Force in schools is very important to strengthen supervision of the implementation of health protocols in schools (Kominfo 2021a), so that the knowledge and skills of the Task Force team in preventing and controlling Covid is very much needed. This study aims to analyze the effect of health education with booklet media and demonstration methods on the knowledge and skills of the Covid-19 Task Force screening at the Global Islamic School Al-Amin Gondanglegi High School, Malang Regency. The design of this study is a pre-experimental design type one group pretest-posttest. The sample is the entire school Covid-19 task force team, totaling 21 people. The results of the paired sample t test obtained a value of Sig (2-tailed) = 0.000 (α0.05), which means that there is an effect of health education with booklet media and demonstration methods on the knowledge and skills of the Covid-19 Task Force screening.